Peran Guru Akidah Akhlak Dalam Meningkatkan Akhlak Peserta Didik - Is Nurhayati, Syifa Aini Tsani (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2020)
The morals of the students at MA Al-Khairiyah Pabuaran are considered to be unfavorable, this can be seen from the way they behave and speak disrespectfully to their teachers, such as against their teachers, do not want to do assignments, and there are still students who do not comply with school rules. This is where the role of the moral teacher is very important, namely by directly modeling good and right behavior, in accordance with the values of the Islamic religion contained in the Koran and Hadith. The purpose of this study is to determine the role of moral teacher in Al-Khairiyah Pabuaran Cilegon MA, to find out the morals of students in MA Al-Khairiyah Pabuaran Cilegon, to find out the method of increasing the morals of students at MA Al-Khairiyah Pabuaran Cilegon, to find out the methods moral enhancement in MA Al-Khairiyah Pabuaran Cilegon, and to find out the role of moral teacher in improving the morals of students in MA Al-Khairiyah Pabuaran Cilegon. The sampling method in this study uses Proposive Sampling techniques. While the data obtained from the results of observations and interviews. The results obtained from the study prove that the morality teacher is very instrumental in improving the morals of students in MA Al-Khairiyah Pabuaran Cilegon. One of the roles of the moral teacher is to give good role models and instill Islamic teachings and values. The morals of the students at MA Al-Khairiyah Pabuaran Cilegon still need to be improved. Therefore the moral teacher applies the method of moral enhancement through tadarus activities before the lesson begins, performs the Read and Write Qur’an (BTQ), performs the obligatory Prayer and the Dhuha Prayer in congregation, and conducts a seven minute Lecture (Kultum).